Cation Chain Length of Nonhalogenated Ionic Liquids Matters in Enhancing SERS of Cytochrome c on Zr-Al-Co-O Nanotube Arrays - Gong, Mian (Langmuir : the ACS journal of surfaces and colloids, 2024)
Surface-enhanced Raman scattering (SERS) is a remarkably powerful analytical technique enabling trace-level detection of biological molecules. The interaction of a probe molecule with the SERS substrate shows important distinctions in the SERS spectra, providing inherent fingerprint information on the probe molecule. Herein, nonhalogenated phosphonium-based ionic liquids (ILs) containing cations with varying chain lengths were used as trace additives to amplify the interaction between the cytochrome c (Cyt c) and Zr-Al-Co-O (ZACO) nanotube arrays, strengthening the SERS signals. An increased enhancement factor (EF) by 2.5-41.2 times compared with the system without ILs was achieved. The improvement of the SERS sensitivity with the introduction of these ILs is strongly dependent on the cation chain length, in which the increasing magnitude of EF is more pronounced in the system with a longer alkyl chain length on the cation. Comparing the interaction forces measured by Cyt c-grafted atomic force microscopy (AFM) probes on ZACO substrates with those predicted by the extended Derjaguin-Landau-Verwey-Overbeek (XDLVO) theory, the van der Waals forces became increasingly dominant as the chain length of the cations increased, associated with stronger Cyt c-ZACO XDLVO interaction forces. The major contributing component, van der Waals force, stems from the longer cation chains of the IL, which act as a bridge to connect Cyt c and the ZACO substrate, promoting the anchoring of the Cyt c molecules onto the substrate, thereby benefiting SERS enhancement